Estimating sheet flow velocities using quinine as a fluorescent tracer: bare, mulched, vegetated and paved surfaces - Zehsaz, Soheil (2022)
When direct flow velocity measurements are not feasible, the use of tracers can be a valuable tool. In the present study, both laboratory and field experiments were conducted to evaluate the applicability of quinine as a fluorescent tracer for estimating mean sheet flow velocities in different ambient light and surface morphology conditions. Quinine excels in low-light conditions when exposed to UVA light. This tracer was compared with dye and thermal tracers, all in liquid form. In these tracing techniques the tracers were injected into the flow, after which surface velocity was estimated by tracking the leading edge of the tracer plumes and applying a correction factor to calculate the mean velocity (in a water column). The visibility of the tracers was evaluated by measuring the relative luminance and contrast ratio of the quinine and dye tracer plumes. Results show that the quinine tracer can be used to estimate sheet flow velocities over a wide variety of soil and urban surfaces; it has better visibility in comparison to the dye tracer but, in some conditions, lower visibility than the thermal tracer. Although quinine is invisible under bright ambient light conditions, this tracer technique requires low-cost experimental setup and is useful in low-light conditions (e.g., night; twilight; shielded environments).